Analisis Kepuasan Mahasiswa Terhadap Kualitas Pelayanan dan Fasilitas Pelayanan Kemahasiswaan di STMIK Budi Darma - Ronda Deli Sianturi (Journal of Business and Economics Research (JBE), 2020)
Higher education competition in Medan City is currently developing very rapidly, this can be seen in every university evaluating and changing every side. One of the most prominent things in the evaluation is service to students, an image of a tertiary institution is considered good depending on whether or not the student service is provided to students. A good image of students is a positive value for universities which is a promotional value for the campus. Good service is a service that can know the desires and needs of people who use it. STMIK Budi Darma is one of the Private Universities who participated in evaluating student services in order to compete with other Private Universities. The purpose of this study is to measure student satisfaction with student services using the Facilities and Quality variables influence student satisfaction. This study used 97 respondents from a total population of 2800 people by testing the Multiple Linear Regression Test, Determination Coefficient Test (R2), Partial Test (t test) and Concurrent Test (F Test).